Anxiety-related responses after sports injury in adolescent athletes: from protective caution to kinesiophobia, sport avoidance and depressive symptoms - a narrative review - Gąska, Anna Agnieszka; Gutkowska, Marta; Jabłońska, Joanna; Wasik, Joanna; Armuła, Marta; Bongege, Claire; Piechowiak, Arkadiusz; Napieraj, Filip; Herc, Bartosz Przemysław; Tesla, Małgorzata (Quality in Sport, 2026)
Background. Sports injuries are frequent among adolescent athletes, especially in organized and competitive sport. Although often treated mainly as orthopedic problems, they may also have psychological consequences. Kinesiophobia, fear of reinjury, sport avoidance and depressive symptoms should be considered within a broader post-injury context. Aim. This narrative review described anxiety-related responses after sports injury in adolescent athletes as a continuum from protective caution to kinesiophobia, sport avoidance and depressive symptoms. Material and methods. A narrative review was conducted using publications on adolescent athletes, sports injury, kinesiophobia, fear of reinjury, fear-avoidance mechanisms, psychological readiness, return to sport, sport avoidance, depressive symptoms, anxiety symptoms, athletic identity and quality of life after injury. Reviews, clinical papers, observational and qualitative studies relevant to sports medicine and sport psychology were included. Results. The literature suggests post-injury responses may include fear of reinjury, kinesiophobia, anxiety, negative mood, loss of motivation and depressive symptoms. Caution after injury may be protective when reinjury risk is relevant or rehabilitation is incomplete. However, persistent fear of movement or reinjury may become maladaptive when it leads to rehabilitation avoidance, delayed sport reintegration, reduced participation or team withdrawal. Adolescents may be vulnerable because injury absence can disrupt athletic identity, peer relationships and future opportunities. Conclusions. Anxiety-related responses in injured adolescents should be understood as a continuum involving physical recovery, psychological readiness, developmental vulnerability, social context and mental health. Rehabilitation should include physical assessment, psychological screening and support when fear, avoidance, low confidence, social withdrawal, loss of motivation or mood symptoms persist.